2017
DOI: 10.1007/s40881-017-0039-9
|View full text |Cite
|
Sign up to set email alerts
|

Bonus versus penalty: How robust are the effects of contract framing?

Abstract: We study the relative effectiveness of contracts that are framed either in terms of bonuses or penalties. In one set of treatments, subjects know at the time of effort provision whether they have achieved the bonus/avoided the penalty. In another set of treatments, subjects only learn the success of their performance at the end of the task. We fail to observe a contract framing effect in either condition: effort provision is statistically indistinguishable under bonus and penalty contracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…We find that both types of incentives lead to increased performance (H1), with no evidence that losses triggered a greater response than gains (H2). This null result echoes those of studies where subjects are told in advance which performance target they have to reach (de Quidt et al, 2017). Another possible explanation lies in the fact that incentives used were relatively small for participants, which has been found to reduce the likelihood of loss aversion (Mukherjee et al, 2017).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…We find that both types of incentives lead to increased performance (H1), with no evidence that losses triggered a greater response than gains (H2). This null result echoes those of studies where subjects are told in advance which performance target they have to reach (de Quidt et al, 2017). Another possible explanation lies in the fact that incentives used were relatively small for participants, which has been found to reduce the likelihood of loss aversion (Mukherjee et al, 2017).…”
Section: Discussionsupporting
confidence: 53%
“…1 For example, some laboratory (Armantier and Boly 2015;Church et al, 2008;Hannan et al, 2005;Imas et al, 2017) and field experiments (Fryer et al, 2012;Hong et al, 2015;Hossain and List 2012) have found that individuals incentivised with contracts framed as losses perform better than those offered equivalent rewards. Meanwhile, other has failed to detect a difference between the two frames (de Quidt et al, 2017;DellaVigna and Pope 2018;Grolleau et al, 2016). 2 A number of studies have considered the effects of different types of incentives for quality (Bracha and Fershtman 2013;Carpenter et al, 2010;Eckartz et al, 2012;Hammermann and Mohnen 2014;Rubin et al, 2018;Shurchkov 2012), while others have studied the effects of incentivising quantity on quality (Al-Ubaydli et al, 2015;Fest et al, 2019;Green, 2014;Greiner et al, 2011;Tonin and Vlassopoulos 2015).…”
Section: Introductionmentioning
confidence: 99%
“…LIONESS Lab was specifically designed for conducting interactive experiments online with participants recruited from crowd-sourcing platforms or from the participant pool of research institutes. However, it can also be used in a laboratory (Arechar et al 2018;Molleman and Gächter 2018), for lab-in-the-field experiments (e.g., Glowacki and Molleman 2017), or to conduct experiments involving non-interactive tasks such as surveys or questionnaires (e.g., de Quidt et al 2017;Gächter et al 2016). An important advantage of this portability is that the screens of experimental participants are exactly the same in the physical lab and online, facilitating comparisons between them.…”
Section: Researchers and Experimental Participants Use Lioness Lab Onmentioning
confidence: 99%
“…Guidelines are available in the online documentation (https://lioness-lab.org/documentation). 4 LIONESS experiments have been used in a number of published studies which were conducted by various research groups with a range of different interactive paradigms (Arechar et al 2018;de Quidt et al 2017;Gächter et al 2016;Glowacki and Molleman 2017;Molleman and Gächter 2018;Stagnaro et al 2017). LIONESS experiments are also being used in a range of ongoing research projects, including experiments with groups of up to 12 participants and over 1,000 participants per session.…”
Section: Researchers and Experimental Participants Use Lioness Lab Onmentioning
confidence: 99%
“…This makes it harder for subjects to learn the task than more commonly used encryption or typing tasks (e.g. Erkal et al, 2011;De Quidt et al, 2017;De Quidt, 2018). This should increase the convexity of costs, which is our primary channel for satisfying our identifiability assumptions.…”
Section: Task and Main Experiments Descriptionmentioning
confidence: 99%